Self-assembled monolayers of isocyanides on nickel electrodes - Lee, Youngu (2005)
Alligator clip on a nickel electrode: Monolayers of ferrocenyl-terminated isocyanides are strongly chemisorbed on nickel surfaces (see picture). The nickel-isocyanide interaction has a parallel binding mode, and the monolayers have higher thermal stability in boiling ethanol than thiol monolayers on gold. The nickel-isocyanide monolayers could be useful in molecular electronics.